Kajian Struktural Dan Nilai Budaya Dalam Cerita Rakyat Suku Dayak Tunjung Rentenuukng Kampung Linggang Melapeh Kabupaten Kutai Barat - Wea, Adelheid Maria; Sulistyowati, Endang; Agustian, Jaka (Adjektiva: Educational Languages and Literature Studies, 2020)
This study aims to describe the structure of the folklore of the Dayak Tunjung Rentenuukng tribe in Linggang Melapeh Village describe the cultural values contained in the folklore of the Dayak Tunjung Rentenuukng tribe in Linggang Melapeh Village. There are three folk tales of the Tunjung Rentenuukng Dayak tribe in Linggang Melapeh Village which were collected and analyzed, namely the story of Lake Aco which can be classified as a local legend. The folklore of Seek and Lokeek is classified into the fairy tale group, and the folklore of the Orphans is classified into the fairy tale group. In general, the folklore of the Dayak Tunjung Rentenuukng tribe in Linggang Melapeh Village has the theme of the formation of a place and the theme of a person's life journey. The characters in the three stories are dominant humans who don't give up easily and have good character. The cultural values contained in the story of the Dayak Tunjung Rentenuukng tribe in Linggang Melapeh Village are the cultural values of human relations with God, human relations with nature, human relations with society, human relationships with other people, and human relationships with oneself.